Samorząd gospodarczy w koncepcji społecznej gospodarki rynkowej w RFN w latach 1949–1963 - Balcerek, Marta (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
After WWII the Federal Republic of Germany needed to choose an economic system for itself which resulted in having to identify a third way – one between liberalism and collectivism. The Ordoliberal concept of social market economics was the best response to the spirit of transformations that occurred in West Germany after 1949. Minister of Economics and former Vice Chancellor, Ludvig Erhard performed market reforms following the spirit of Ordoliberalism over the period of 1949-1963. The purpose of this paper is to make Polish readers acquainted with the model of a social market economy, i.e. a market economy including social responsibility, implemented by the units of economic self-government – chambers of commerce and industry, chambers of agriculture and of crafts.